2020
DOI: 10.1177/1464420719899685
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the surface quality of friction stir welds by the analysis of process data using Artificial Neural Networks

Abstract: Friction stir welding is an advanced joining technology that is particularly suitable for aluminum alloys. Various studies have shown that welding quality depends significantly on the welding speed and the rotational speed of the tool. It is frequently possible to detect an unsuitable setting of these parameters by examining the resulting surface defects, such as increased flash formation or surface galling. In this work, Artificial Neural Networks were used to analyze process data in friction stir welding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…In Hartl et al [15], the focus was on the indirect monitoring of the surface quality. Various sensors were employed for the inline acquisition of accelerations, forces, the spindle torque, and temperatures.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In Hartl et al [15], the focus was on the indirect monitoring of the surface quality. Various sensors were employed for the inline acquisition of accelerations, forces, the spindle torque, and temperatures.…”
Section: Related Workmentioning
confidence: 99%
“…For the RNN, the instantaneous frequency [19] and the spectral entropy, which are also often used as a feature in medicine signal processing [20], were determined and employed as input. For the CNN, spectrograms were generated, similar to Hartl et al [15]. Spectrograms depict the spectral density of a signal depending on the time and the frequency in a three-dimensional manner [21].…”
Section: Data Acquisition and Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Important process parameters to control the surface topography of friction stir welds are the welding speed and the rotational speed of the tool [22]. Hartl et al [23] presented key indicators for quantifying the surface topography of friction stir welds and showed that some of these can be predicted by evaluating process variables such as the process forces or temperatures [24].…”
Section: State Of the Art-evaluation Of The Surface Of Friction Stir mentioning
confidence: 99%
“…Mishra et al [12] predicted the corrosion potential of friction stir welded joints by using back propagated artificial neural network. Hartl et al [13] used artificial neural networks for the surface quality of friction stir welded joints. Rehim et al [14] predicted and simulated the Vickers hardness of friction stir welded joints by using artificial neural network.…”
Section: Y = (1)mentioning
confidence: 99%